Operasional Rahmat Sakramen Tobat Bagi Kesadaran Akan Dosa Dalam Jiwa Peniten Menurut Thomas Aquinas - Herwindo Chandra (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2024)
Two understandings of the reality of grace in the Sacrament of Penance were found. The Sacrament of Penance is a sign and means of the flow of grace of repentance in the soul of the penitent. However, in the penitent there is the reality of the grace of the Holy Spirit thanks to the Sacrament of Baptism. At first glance, both are like two separate realities of grace. Therefore, this article attempts to identify the relationship between the two in the operational scope of grace. This fills in several studies that have found various responses from Catholics to the Sacrament of Penance. So the purpose of this article is to understand the relationship between the grace of the Holy Spirit in the penitent and the operational grace of the Sacrament of Penance. Achieving this goal also leads to the novelty of the article, namely the fundamental reasons for the penitent's inappropriate attitude towards the Sacrament of Penance. The method of analysis of sacramental grace and baptism uses the desk research method based on the thoughts of Saint Thomas Aquinas. Through Aquinas's framework of thought on the Sacrament of Penance, this article has a new emphasis on psychological awareness that leads individuals to true regret and repentance. The findings of the analysis reveal that problematic psychological unconsciousness can make penitents unaware of the roots of sin so that true regret is difficult to achieve. The theoretical implications of this writing are the strengthening of catechesis of the Sacrament of Penance on the aspect of psychological unconsciousness. At the same time, it enriches the pastoral accompaniment of the Sacrament of Penance in the field of kerygma.